Human Papillomavirus Genotype Distribution and Human Papillomavirus 16 and Human Papillomavirus 18 Genomic Integration in Invasive and In Situ Cervical Carcinoma in Human Immunodeficiency Virus-Infected Women. Issue 8 (1st November 2011) - Darwich, Laila; Cañadas, María-Paz; Sirera, Guillen; Alameda, Francesc; Forcada, Pilar; Delas, Jordi; Fernández, Inés; Llatjós, Mariona; Coll, Josep; Clotet, Bonaventura; Videla, Sebastià
Abstract : Background: Women infected with human immunodeficiency virus (HIV) are at increased risk of developing precancerous and cancerous lesions in cervix because of persistence of oncogenic human papillomavirus (HPV) infection. Scarce information about the HPV genotypes attributed to cervical cancer in the HIV-infected population is available, especially in countries with a low prevalence of this pathology. Objective: The objective of the study was to assess the prevalence and distribution of HPV types, and the viral integration of HPV-16 and HPV-18 in cervical squamous cell carcinoma of HIV-infected and HIV-negative women. Methods: A total of 140 formaldehyde-fixed paraffin-embedded specimens from 31 HIV-infected and 109 matched HIV-negative women, with a diagnosis of in situ or invasive cervical carcinoma, were identified between 1987 and 2010 from different hospitals of the Barcelona area, Spain. Human papillomavirus genotyping and integration were analyzed by standardized polymerase chain reaction. Results: Similar prevalence and distribution of HPV genotypes were detected in cervical cancers (in situ and invasive) regardless of HIV condition. The most common types were as follows: HPV-16 (58% in HIV-positive vs 72% in HIV-negative) and HPV-33 (16% vs 8%). In invasive cervical carcinoma, HPV-18 was significantly more prevalent in HIV-positive women (14% vs 1%; P = 0.014). The proportion of samples with integrated forms of HPV-16 (39% vs 45%) and HPV-18 (50% vs 50%) was similar in both groups. Conclusions: The prevalence and distribution of principal HPV types involved in the carcinogenesis process of the cervix were similar in HIV-infected and noninfected women, although a tendency toward a lower HPV-16 and a higher HPV-18 prevalence in invasive cervical carcinoma was detected in HIV-positive women. Similar percentage of HPV-16 and HPV-18 viral integration was found in formaldehyde-fixed paraffin-embedded specimens of cervical cancer regardless of the HIV infection status.